2016
DOI: 10.1016/j.ecoleng.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing pentachlorophenol degradation by vermicomposting associated bioremediation

Abstract: Enhancing pentachlorophenol degradation by vermicomposting associated bioremediation", for the consideration as Short Communication in Ecological Engineering. This study investigated the roles and mechanisms of earthworm (Eisenia foetida) on soil pentachlorophenol (PCP) degradation under sterile and non-sterile soil-compost condition. The vermicomposting technology has the potential to enhance the bioremediation of PCP contaminated soil, which was first time revealed in this study to our knowledge. All the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…between microorganisms and reactants (Lin et al, 2016b). Additionally, earthworms also increase soil microbial activities via digesting organic matters and improving nutrient availability (Lin et al, 2016a). Thus, vermicomposting treatments with earthworms can ameliorate soil properties, offset the limitations in bioaugmentation, and consequently improve the pollutants removal efficiency (Li et al, 2015;Lin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…between microorganisms and reactants (Lin et al, 2016b). Additionally, earthworms also increase soil microbial activities via digesting organic matters and improving nutrient availability (Lin et al, 2016a). Thus, vermicomposting treatments with earthworms can ameliorate soil properties, offset the limitations in bioaugmentation, and consequently improve the pollutants removal efficiency (Li et al, 2015;Lin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, earthworms also increase soil microbial activities via digesting organic matters and improving nutrient availability (Lin et al, 2016a). Thus, vermicomposting treatments with earthworms can ameliorate soil properties, offset the limitations in bioaugmentation, and consequently improve the pollutants removal efficiency (Li et al, 2015;Lin et al, 2016a). Lin et al (2016a) reported earthworms significantly enhance the pentachlorophenol (PCP) degradation by improving soil physicochemical properties and increasing microbial biomass and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Vermicompost also degraded pentachlorophenol (PCP), a chemical used in an agricultural field. The degradation of the PCP was made possible through the presence of the humic fraction of the vermicomposts and the formation of a PCP–humus complex, which was then decomposed by neutralizing the pH of the soils (Lin et al., ).…”
Section: Environmental Benefits Of Vermicompostmentioning
confidence: 99%
“…Vermicompost also degraded pentachlorophenol (PCP), a chemical used in an agricultural field. The degradation of the PCP was made possible through the presence of the humic fraction of the vermicomposts and the formation of a PCP-humus complex, which was then decomposed by neutralizing the pH of the soils(Lin et al, 2016).Vermicompost microbial activities have resulted in reductions in concentrations of various herbicides and heavy metals present in the soils. Vermicompost application decreased the concentration of cadmium ion (1+) (Cd + ) and copper ion (1+) (Cu + ) in tropical soils(Jordão et al, 2011).…”
mentioning
confidence: 99%
“…The ratio of 5-day biological oxygen demand (BOD 5 ) to chemical oxygen demand (COD), designated as B/C, can be significantly reduced by industrial wastewater to <0.3, indicating a poor biodegradability and causing the paralysis of the biochemical treatment units [20,21]. Due to the shock load and intermittent impacts of PTEs, cyanide and other toxic substances in industrial wastewater, WWTPs might lose efficiencies in removing pollutants to some extent and the effluent quality is affected [21,22], consequently increasing the operation cost [23]. It is therefore necessary to monitor the industrial shock load and improve the resistance of WWTPs to maintain the removal efficiency of refractory pollutants.…”
Section: Introductionmentioning
confidence: 99%